Motivasi Intrinsik Member Mengikuti Latihan Beban di Fitness X Denpasar Dalam Perspektif Self-Determination Theory - Muhtadin, Ahmad; Hartika, Listiyani Dewi; Dewi, Ni Nyoman Ari Indra (JURNAL PSIKOLOGI MANDALA, 2025)
This research aimed to understand intrinsic motivation in individuals who engaged in weight training/fitness at Fitness X Denpasar based on Self-Determination Theory. The research used a descriptive quantitative approach, involving 161 members of Fitness X Denpasar who were selected through a probability sampling technique. The research employed a survey method with a Likert scale based on Self-Determination Theory (autonomy, relatedness, and competence) to measure the intrinsic motivation of Fitness X Denpasar members. After undergoing validity and reliability tests, the scale yielded 21 valid items with a Cronbach's Alpha of 0.968, which indicated high reliability. The results showed that, based on demographic characteristics (gender, age, education, and occupation), the majority of respondents at Fitness X Denpasar had intrinsic motivation that fell into the high to very high category according to Self-Determination Theory. This descriptive analysis indicated that the intrinsic motivation of individuals for weight training at Fitness X Denpasar was generally high according to Self-Determination Theory, with an average score of 75.80 and the majority of respondents in the high to very high categories. These findings affirmed that self-determination played a crucial role in shaping and maintaining individuals' intrinsic motivation for engaging in fitness training.